Temporal analysis of rat growth plates: cessation of growth with age despite presence of a physis. - Roach, H; Mehta, G; Oreffo, R; Clarke, N; Cooper, C (2003)
Despite the continued presence of growth plates in aged rats, longitudinal growth no longer occurs. The aims of this study were to understand the reasons for the cessation of growth. We studied the growth plates of femurs and tibiae in Wistar rats aged 62-80 weeks and compared these with the corresponding growth plates from rats aged 2-16 weeks. During skeletal growth, the heights of the plates, especially that of the hypertrophic zone, reflected the rate of bone growth. During the period of decelerating growth, it was the loss of large hydrated chondrocytes that contributed most to the overall decrease in the heights of the growth plates. In the old rats we identified four categories of growth plate morphology that were not present in the growth plates of younger rats: (a). formation of a bone band parallel to the metaphyseal edge of the growth plate, which effectively sealed that edge; (b). extensive areas of acellularity, which were resistant to resorption and/or remodeling; (c). extensive remodeling and bone formation within cellular regions of the growth plate; and (d). direct bone formation by former growth plate chondrocytes. These processes, together with a loss of synchrony across the plate, would prevent further longitudinal expansion of the growth plate despite continued sporadic proliferation of chondrocytes.